2003
DOI: 10.1007/s11920-003-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

The other side of estrogen replacement therapy: Outcome study results of mood improvement in estrogen users and nonusers

Abstract: The effect of estrogen on the brain and body of women is a controversial topic that has received a tremendous amount of attention in the past few years. Recent reviews have focused on hormone replacement therapy (HRT), medical risks, and effects on brain metabolism, cognition, risk of Alzheimer's disease, and mood. This article summarizes HRT and mood improvement in postmenopausal women. For nondepressed women, experimental designs provide no clear evidence for mood improvement associated with HRT, whereas obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…Neuropsychiatrists have also conceded that 'there is a clear need to examine the necessary duration of HRT for neuroprotection to decrease a woman's risk for depression, cognitive dysfunction and development of Alzheimer's disease' 44 .…”
Section: Climacteric Depressionmentioning
confidence: 99%
“…Neuropsychiatrists have also conceded that 'there is a clear need to examine the necessary duration of HRT for neuroprotection to decrease a woman's risk for depression, cognitive dysfunction and development of Alzheimer's disease' 44 .…”
Section: Climacteric Depressionmentioning
confidence: 99%
“…A. Morgan et al, 2004), spatial learning (H. N. Fugger et al, 1998), mood and cognition (K. J. Miller, 2003; C.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies (Zweifel and Obrien, 1997;Miller, 2003) suggest that HRT augments serotonergic activity and facilitates the improvement of clinical depression and the efficacy of antidepressants, other studies (Pearce et al, 1997) do not report an antidepressant effect from HRT. This study showed that HRT alone did not alleviate depressive symptoms in menopausal women.…”
Section: Discussionmentioning
confidence: 99%